The Influence of Islamic Financial Literacy and Service Quality on Customers’ Decisions to Use Islamic Banking Products with Religiosity as a Mediating Variable - Annastasya Aprilia Ariyanto; Muhammad Sholahuddin (Paradoks : Jurnal Ilmu Ekonomi, 2026)
This investigation explores the dynamics between Islamic financial literacy and the quality of banking services in shaping customers' decisions about Islamic banking products, with religiosity as a pivotal mediator. Using a quantitative lens, the research employs a causal-associative design and leverages path analysis via Partial Least Squares Structural Equation Modeling (PLS-SEM) in SmartPLS 4.0. The study scrutinized a purposively chosen cohort of 200 active clients of Islamic banks. Results demonstrate that superior service quality exerts a robust, direct, and favorable influence on customers’ choices. In contrast, Islamic financial literacy, despite its positive orientation, does not have a statistically significant effect. Intriguingly, both literacy in Islamic finance and service excellence substantially cultivate religiosity, which, in turn, exerts a pronounced positive impact on banking decisions. Religiosity also emerges as a crucial mediating mechanism linking financial literacy and service quality to customers’ adoption behavior. The novelty of this work lies in its integrative framework that accounts for both rational determinants (knowledge and service) and spiritual drivers (religiosity) in Muslim consumer behavior toward Islamic banking offerings. In practice, these findings advocate a strategic synthesis of educational initiatives, exemplary service delivery, and spiritual alignment to reinforce customer commitment, satisfaction, and lasting loyalty.